Beyond air-sea battle the debate over US military strategy in Asia - Friedberg, Aaron L. 1956- (Adelphi (Series) (International Institute for Strategic Studies), 2014)
This book presents the first comprehensive analysis of the debate over how the United States and its allies can counter China's rapidly growing military power.